PENGARUH SPI, SAKD, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH DAERAH - Chair, Zalsa Bila Maulida Kemal; Tarjo (APSSAI ACCOUNTING REVIEW, 2024)
Research aims: This research aims to determine the influence of the internal control system, regional financial accounting system, and information technology on the quality of financial reports in the Bangkalan Regency Government. Design/Methodology/Approach: The sample selection method used purposive sampling and obtained a sample of 89 respondents from Bangkalan Regency Government. The analysis technique uses multiple linear regression and is processed using SPSS Statistics 23.0. Research findings:  This research indicates that the internal control system and the use of information technology significantly affect the quality of financial reports. Meanwhile, the regional financial accounting system does not affect the quality of financial reports. Theoretical contribution/Originality: This study introduces a new variable, namely Utilization of Information Technology, to examine the impact of internal control systems, regional financial accounting systems, and the utilization of information technology on the quality of financial reporting in local governments in urban areas. Practitioner/Policy implication: The study offers recommendations for local governments to enhance internal controls, optimize regional financial accounting systems, and utilize technology to improve financial reporting quality. These findings can also guide policymakers in creating regulations that promote accountability and transparency in financial management practices.